Influence of Rayleigh Number in Turbulent and Laminar Region in Parallel-Plate Vertical Channels - Abdulbari, Hayder A.; Abd Al-Rubai, Rana Thabet (Knowledgia Review, Malaysia, 2008)
The main objectives of this research is to study the influence of Rayleigh number in turbulent and laminar region in parallel-plate vertical plate so we will comparison the different between laminar and turbulence in Rayleigh number and validate it with existing experimental data available in literature. The channel was formed by two vertical parallel plates. Velocity measurements were carried out for natural convection flow in a symmetrically heated vertical channel. The plates taken were 12.5 mm thick the modified Rayleigh number (Ram) range 50 to 1x107 has been covered for symmetrically heated isothermal vertical surfaces. The aspect ratio of the channel was kept constant (L/b = 12) and width 200 mm. One plate was kept at fixed temperature above and the other at fixed temperature below the ambient temperature and local velocity and temperature profile at three different sections of channel were reported along with the local heat transfer coefficients and temperature distribution on the heated wall.